Regimens of EM/CO in treatment of hish-risk gestational trophoblastic neoplasms - Hoang, Bao Nhan; Le, Sy Phuong; Dinh, Thi Phuong Minh; Hoang, Le Nhi; Le, Thi Y Nhan; Hoang, Thi Huong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
Objectves: 1) To study signs and symptom of high risk gestational trophoblastic neoplasms 2) Role of multi-agents chemotherapy in treatment of high-risk patients. Methods: A perspective study. Materials: 25 patients who had high-risk gestational trophoblastic neoplasms were treated in department of Obstetrics and Gynecology, Hue Central Hospital. Results: Mean age of patients was 28.3±7.5, risk-score was 8.6±0.8, number of cycles of chemotherapy was 8.3±3.4, rate of success of the regimen was 96%, only 28% of patients had total hysterectomy, 100% of patients had side-effects, of that the most common was hair-loss. 12 pateints were pregnant after treatment, 41.7% of them reached term pregnancy. Conclusion: Multi-agents chemotherapy with EM/CO regimen is safe and effective in treatment of high- risk gestaional trophoblastic neopalsia.